Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 5 - Section 5.6 - Special Products - Exercise Set - Page 388: 46



Work Step by Step

$(a^{2}+6)(a^{2}-6)$ To evaluate this product, use the following formula: $(x-y)(x+y)=x^{2}-y^{2}$ Here, $x=a^{2}$ and $y=6$ $(a^{2}+6)(a^{2}-6)=(a^{2})^{2}-(6)^{2}=a^{4}-36$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.